2019
DOI: 10.1177/2516598419862676
|View full text |Cite
|
Sign up to set email alerts
|

Nano-finishing of MEMS-based platforms for optimum optical sensing

Abstract: The surface finish of the microelectromechanical systems substrate, particularly the ones that are deployed in chip-based optofluidic systems, is of utmost importance, and the overall surface finish helps in preventing light scattering and associated losses. The proposed system is made up of a microchannel with a coating on its interior which acts as a cladding layer and possesses an air-like refractive index. The water-based solutions with refractive indices higher than the coating, when confined within such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Microfabrication techniques were successfully used to miniaturize the device size by fabricating a gas sensor. These techniques can be used for either bulk or surface micromachining of silicon in order to integrate multiple components on a single wafer [18]. The fabrication of sensors over silicon substrates typically involves the repetitive uses of the following techniques; such as deposition, photolithography, and etching [19,20].…”
Section: Fabrication Of Mems Gas Sensormentioning
confidence: 99%
“…Microfabrication techniques were successfully used to miniaturize the device size by fabricating a gas sensor. These techniques can be used for either bulk or surface micromachining of silicon in order to integrate multiple components on a single wafer [18]. The fabrication of sensors over silicon substrates typically involves the repetitive uses of the following techniques; such as deposition, photolithography, and etching [19,20].…”
Section: Fabrication Of Mems Gas Sensormentioning
confidence: 99%
“…Hara et al deposited an AlN film using RF magnetron reactive sputtering technique that gives lower process temperature than CVD [94]. Gupta et al reported an optical sensing work with a surface coating of porous polymer-film; a reduction in surface-roughness up to 33 nm is obtained in contrast to the 235 nm surface-roughness of uncoated surfaces, which in turns reduces 27.42% relative transmission losses [95]. Prior to the deposition step, a high temperature baking step is performed to breaks down the SiO2 layer and allows the Si to reflow and smooth the surface features and finally leave the Si with a low-surface roughness [96].…”
Section: Deposition Processmentioning
confidence: 99%
“…The development of the microfluidic systems components is associated with the microtechnology based on silicon materials. They were developed after the discovery of deep etching and bonding methods [1], [2], which allow to realize microchannels in silicon [3], [4], glass [5], [6], polymer material polydimethylsiloxane (PDMS) [7], [8] and SU-8 [9].…”
Section: Introductionmentioning
confidence: 99%